Wheel track loosening can reduce the risk of pesticide leaching to surface waters. (27th September 2020) - Vuaille, Jeanne; Daraghmeh, Omar; Abrahamsen, Per; Jensen, Signe M.; Nielsen, Søren Kirkegaard; Munkholm, Lars J.; Green, Ole; Petersen, Carsten T.
Abstract: Wheel tracks can lower topsoil infiltrability and increase water ponding in agricultural fields. A seedbed harrow mounted with two goosefeet tine points, the eradicators, was used to investigate track loosening at different depths on a sandy loam soil as a way of mitigating compaction effects and reducing the risk of pesticide transport to surface waters. Loosening strongly affected air permeability and steady‐state infiltration. The agro‐ecological system model Daisy was used to simulate the effects of soil structural and hydraulic changes on pesticide leaching to subsurface drain lines over a 332‐year period. Measured properties of the topsoil were combined with a representative subsoil and weather series and with realistic management scenarios. The loads of pesticide in the drains for 3 months after loosening were calculated for each year, and the risk was defined as the 90th percentile of the load. We focused on three different herbicides used in sugar beet cultivation in spring: glyphosate, metamitron and phenmedipham. Our simulations showed that for all pesticides loosening could lower the risk by 10% on average for a 3‐m working width, and the tracks contribution to the risk by 34%, for all drain spacing and working width settings. Wheeling did not affect the risk but this result was sensitive to the parameterization of the hydraulic conductivity in the compacted soil layer, showing potentially higher risk under certain conditions. These results showed that wheel track loosening is an effective strategy for reducing the risk of surface water contamination from pesticides used in agriculture. Abstract : Wheel track loosening can foster water infiltration and reduce pesticide leaching through drain‐connected biopores.